Assessing Evolution and Biodiversity in Plants at the Molecular Level - Brinegar, Chris (Kathmandu University Journal of Science, Engineering and Technology, 2009)
DNA sequencing and fingerprinting methods for the analysis of plant evolution and diversity have been in use for over two decades. Thousands of research reports have been published which have provided insight not only into the evolutionary pathways of plant species but also into the evolution of several genetic loci. This review highlights several articles that have made use of nuclear and chloroplast loci to investigate plant phylogeny and the evolutionary processes that have led to the current distribution and diversity of plants.